The Economic transformation of the Tugen women in the colonial period - Chepchieng, Mary (Kabarak University, 2016)
The current thinking on development issues indicates that there is a gender imbalance in access to and control over resources in most African communities (Snyder, 2000) In communities like the Keiyo of Kenya, women were priestesses who carried out same rituals as men (Changkwony, 1999) The Tugen household in the pre-colonial period was the primary unit of production and reproduction (Ochieng, 1975) The British colonial penetration produced the most profound changes in their lives and disrupted the traditional system of acculturation reflected by the changing family structure and patterns of behaviour
Keywords: Economic transformation; colonial period